Potensi Ekstrak Spirulina sp. Sebagai Imunostimulan Pada Bidang Akuakultur: The Potential of Spirulina sp. Extract as an Immunostimulant in the Aquaculture Field - Nuri Muahiddah; Rangga Idris Affandi (LPPM Universitas Mataram, 2023)
Aquaculture is an important industry that plays a role in meeting the world's animal protein needs. One of the main challenges in aquaculture is maintaining the health of cultivated aquatic organisms. Spirulina, a type of nutrient-rich blue-green microalgae, has garnered attention as a natural immunostimulant capable of enhancing the immune system of aquatic organisms. This article explains the immunostimulant properties of spirulina, including the bioactive compounds it contains, such as polysaccharides, proteins, photosynthetic pigments, and lipopolysaccharides. These compounds can boost the production of immune cells and phagocytic activity, which can help aquatic organisms combat pathogens. Furthermore, the article discusses the potential benefits of using spirulina extract in aquaculture, including increased resistance to diseases, faster growth, and improved nutritional quality of aquatic organisms. However, there are also challenges to address, such as determining the appropriate dosage and optimal application methods. This article contributes to the understanding of how spirulina extract can be utilized to enhance the health and productivity of aquatic organisms in aquaculture. With further research and the development of improved application methods, the potential of spirulina extract as an immunostimulant in aquaculture can be more fully realized, helping to meet the increasing global demand for protein.